Impact of hysteresis of unsaturated hydraulic properties on rainfall-induced slope failures - Natalia, Levinna; Yang, Jun (Engineering geology, 2025)
The devastating consequences of rainfall-induced slope failures call for considering more realistic scenarios in slope engineering. As the matric suction in unsaturated soil varies with climatic conditions, hysteresis behavior is observed in the drying (desorption) and wetting (adsorption) processes. The soil water characteristic curve (SWCC) is essential in describing the relationship between the water content and matric suction. Previous studies contained diverging views on selecting SWCC for slope stability analysis, particularly concerning the hysteresis behavior. Here we present an investigation into the impact of hysteresis in SWCC on the stability of unsaturated soil slopes. Different SWCC shapes, designed to compare the influence of selecting drying and wetting curves on rainfall-induced landslides under various rainfall characteristics, permeability, and initial suction, are examined. We observe that the SWCC resembling the characteristic of the drying curve results in more critical conditions and more significant fluctuations in safety factor when subjected to rainfall and no-rainfall events. The magnitude of initial suction relative to the air-entry value potentially explains the diverging views in the literature of whether the drying or wetting curve ensures a safer slope stability analysis. The findings from this study have significant implications for slope stability evaluation, particularly emphasizing the importance of considering hysteresis, heterogeneity, parameter uncertainty in design. •The possible reason for diverging views on the impact of SWCC hysteresis on slope stability analysis is explored.•The role of SWCC shape in slope stability under various rainfall patterns is evaluated in detail.•The role of initial suction and SWCC selection is examined, and the implications for slope stability evaluations are discussed.